Highly efficient green synthesis of α-hydroxyphosphonates using a recyclable choline hydroxide catalyst. (25th May 2017) - Kalla, Reddi Mohan Naidu; Zhang, Yu; Kim, Il
Abstract : Aldehydic carbonyl groups are eco-friendly and efficiently hydrophosphonylated by diethylphosphite using the basic ionic liquid, choline hydroxide. Abstract : Choline hydroxide has been found to be an efficient basic ionic liquid catalyst for the synthesis of α-hydroxyphosphonates. Hydrophosphonylation of aldehydes was performed via the nucleophilic addition of diethylphosphite to aldehydic carbonyl compounds, in the presence of choline hydroxide under neat as well as solvent conditions. A wide array of substrates, including aromatic, fused aromatic, and heterocyclic aldehydes, were efficiently converted to their corresponding products in good yields. This protocol provides an alternative method for the straightforward synthesis of α-hydroxyphosphonates in high yields.